2007
DOI: 10.1093/jxb/erl274
|View full text |Cite
|
Sign up to set email alerts
|

Auxin response, but not its polar transport, plays a role in hydrotropism of Arabidopsis roots

Abstract: Plants are sessile in nature, and need to detect and respond to many environmental cues in order to regulate their growth and orientation. Indeed, plants sense numerous environmental cues and respond via appropriate tropisms, and it is widely accepted that auxin plays an important role in these responses. Recent analyses using Arabidopsis have emphasized the importance of polar auxin transport and differential auxin responses to gravitropism. Even so, the involvement of auxin in hydrotropism remains unclear. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 28 publications
(37 reference statements)
1
83
1
Order By: Relevance
“…The spatial distribution of roots, including primary and lateral roots, largely depends on environmental signals, such as water availability, gravity, and light, which are perceived by the root apex (Kiss et al, 2002(Kiss et al, , 2003Kobayashi et al 2007) and modulate regional cell elongation rates via mechanisms that involve auxins (Swarup et al, 2005;Kaneyasu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution of roots, including primary and lateral roots, largely depends on environmental signals, such as water availability, gravity, and light, which are perceived by the root apex (Kiss et al, 2002(Kiss et al, , 2003Kobayashi et al 2007) and modulate regional cell elongation rates via mechanisms that involve auxins (Swarup et al, 2005;Kaneyasu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our recent demonstration showed that polar auxin transport is not essential for root hydrotropism in Arabidopsis. Namely, Arabidopsis roots treated with inhibitors of auxin efflux, TIBA or NPA, showed normal hydrotropic response, while their gravitropic response was substantially reduced (Kaneyasu et al, 2007). Also, hydrotropic response of pin2/wav6-52 mutant roots in which polar auxin transport and gravitropism were altered, did not differ from that of wild-type roots (Takahashi et al, 2002).…”
Section: Wild-type Plants With Bfa At a Concentration Of 10mentioning
confidence: 93%
“…Further complementation analyses were performed as described previously . Treatment with BFA was performed as previously described (Kaneyasu et al, 2007), with the exception that the stock solution of BFA (Sigma Chemicals) was prepared at a concentration of 1,0003 in dimethyl sulfoxide. As a control, an equivalent volume of dimethyl sulfoxide was added to the culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…2A and B). An inhibitor of auxin response reduced hydrotropism, 12 and also inhibited auxin-dependent DR5::GUS expression. 15 However, a decrease of DR5::GUS in wt root tips was not an impediment for developing an hydrotropic response.…”
mentioning
confidence: 94%
“…4 Furthermore, current pharmacological studies using inhibitors also indicated that both auxin influx and efflux are not required for hydrotropic response whereas auxin response is necessary for it. 12 These authors suggested a novel mechanism for auxin in root hydrotropism. Here, we analyzed whether asymmetric auxin distribution takes place across hydrotropicallystimulated roots using transgenic plants carrying a responsive auxin promoter (DR5) driving the expression of ß-glucuronidase (GUS) or green fluorescent protein (GFP) 13,14 in wt and nhr1 backgrounds.…”
mentioning
confidence: 99%